Pengembangan Bahan Ajar Digital: Upaya Mendorong Kreativitas Guru-Guru Di Kota Tangerang Selatan - Marisa Marisa; Dewi Artati Padmo Putri; Suryo Prabowo; Siti Nafsiah; Sutaryanto Sutaryanto (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2023)
Abstract: Technological sophistication, making interactive digital teaching materials easier. Interactive digital teaching materials make it easier for students to study independently according to their abilities and learning speed. Currently the ability of teachers in South Tangerang still needs to be improved in blinding Interactive Digital Teaching Materials. The community service program provided to participants is carried out using a combination of online training and mentoring methods, combined with face-to-face meetings. In general, training and assistance for the development of Interactive Digital Teaching Materials gave good results, where 75% of participants completed their products. Participants also expressed satisfaction with the program. This condition can be said to be good, but to further increase participant satisfaction in the next training, input from participants can be considered.            Keywords: digital teaching materials; learn to be independent; teaching materials  Abstrak: Kecanggihan teknologi, membuat bahan ajar digital interaktif menjadi lebih mudah. Bahan ajar digital interaktif memudahkan siswa belajar mandiri sesuai dengan kemampuan dan kecepatan belajarnya. Saat ini kemampuan guru di Tangerang Selatan masih perlu ditingkatkan dalam membutakan Bahan Ajar Digital Interaktif. Program pengabdian kepada masyarakat yang diberikan kepada peserta dilakukan dengan menggunakan kombinasi metode pelatihan dan pendampingan secara daring, dipadukan dengan pertemuan tatap muka. Secara umum pelatihan dan pendampingan pengembangan Bahan Ajar Digital Interaktif memberikan hasil yang baik, dimana 75% peserta menyelesaikan produknya. Peserta juga menyatakan puas dengan program tersebut. Kondisi ini dapat dikatakan baik, namun untuk lebih meningkatkan kepuasan peserta pada pelatihan selanjutnya, masukan dari peserta dapat menjadi pertimbangan. Kata kunci: bahan ajar; bahan ajar digital; belajar mandiri